Use of Music Pedagogy Experiences in Improving the Professional Skills of Music Teachers of General Secondary Schools - Abdumutalibovich, Ma’rufjon Ashurov (Indonesian Journal Publisher, 2024)
This scientific article was published on the basis of the principles of using music pedagogy experiences in improving the professional skills of music teachers of general secondary schools at the end of the dissertation work. This study investigates the diverse impacts of music on human life, emphasizing its role in shaping emotions and behaviors. It underscores the significance of music pedagogy in developing effective teaching strategies and approaches. The methodology combines descriptive and explanatory elements, incorporating a literature review and practical examples. Results emphasize the importance of constant self-education for music educators. The study explores various teaching approaches, including integrative, active music playing, constructivist, cultural, and individual methods. It recognizes the value of both individual and group lessons, along with the integration of modern technologies in music education. The organization of the educational process is highlighted, focusing on goal-setting, regular practice, constructive feedback, and creating a supportive learning environment. Overall, the study offers insights into impactful music teaching strategies and methodologies.